PHYSIOLOGICAL BASIS OF HIGHER NERVOUS ACTIVITY - Mirsiddikova N.M., Ergasheva M.A., Koriyev S.A., (Central Asian Journal of Medicine, 2025)
This article presents the results of a scientific study dedicated to the physiological foundations of higher nervous activity. Higher nervous activity refers to the process by which an organism interacts with the external environment, processes information received through sensory organs, and generates a response. The study explores the main principles of higher nervous activity, its physiological mechanisms, and biological significance.